How does digitalization promote productivity growth in China? - Kaixuan Bai; Zhiyang Shen; Shuyuan Zhou; Zihan Su; Rongrong Yang; Malin Song (Journal of Innovation & Knowledge)
In the context of Industry 4.0, advancements in computer technology and the digital revolution have profoundly impacted global economic growth. As digitalization assumes an increasingly critical role, this study innovatively integrates digital capital as a fundamental input, alongside labor and traditional capital, into non-parametric production technologies to evaluate the Luenberger-Hicks-Moorsteen total factor productivity(TFP) indicator. This approach provides a novel perspective on productivity growth in China during the digitalization era. Furthermore, a new input-based decomposition of the productivity indicator is proposed to identify the driving forces behind China's rapid economic expansion. The factors influencing productivity change and its decomposition components are further analyzed. Utilizing panel data from 30 provinces in China covering the period from 2012 to 2021, the findings reveal that overall productivity growth in China increased by 2.73 % during the sample period, with contributions of 64.97 % from labor and 35.01 % from digital capital. Conversely, the contribution rate of non-digital capital to TFP growth was -0.02 %. This suggests that China's economic growth is primarily driven by labor, followed by digital capital, while the influence of traditional capital is diminishing. Furthermore, the regression results underscore the significant contribution of digital economy development to TFP growth.